2016
DOI: 10.2527/jas.2016-0693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding fermented wheat with Lactobacillus reuteri on gut morphology, intestinal fermentation, nutrient digestibility, and growth performance in weaned pigs1

Abstract: Feeding fermented feed to weaned pigs may improve nutrient digestibility and gut health and thereby reduce diarrhea incidence. Effects of feeding wheat grain fermented for 24 h with were evaluated with 36 weaned pigs (7.3 kg BW). Fermented wheat grain contained (DM basis) 14.2% CP, 0.45% chemically available Lys, and 7.8% NDF, whereas unfermented wheat grain contained 16.4% CP, 0.45% chemically available Lys, and 9.9% NDF. Pigs were fed 6 mash wheat-based diets balanced for water content during 2 phases: Phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Intestinal crypts are invaginations of the epithelium around the villi that are lined by epithelial cells that secrete enzymes. The base of each crypt is constantly dividing to maintain the structure of the villus . Therefore, an increase in crypt depth produces more developed villi .…”
Section: Discussionmentioning
confidence: 57%
“…Intestinal crypts are invaginations of the epithelium around the villi that are lined by epithelial cells that secrete enzymes. The base of each crypt is constantly dividing to maintain the structure of the villus . Therefore, an increase in crypt depth produces more developed villi .…”
Section: Discussionmentioning
confidence: 57%
“…Likewise, a Lactobacillus acidophilus supplementation increased linearly the apparent digestibility of N, possibly through the stimulation of the hindgut fermentation [ 67 ]. Such a stimulation could be primarily due to the exopolysaccharides produced by Lactobacillus [ 68 ]. However, Lactobacillaceae are also known to improve the health of the small intestine in humans as in animals [ 69 , 70 ] as a probiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Considering today's reduction in the weaning time of piglets (Niekamp et al 2007;Smith et al 2010;Xiao et al 2014) and its effect on the animals' underdeveloped immune and digestive systems, probiotic fermented feed additives have been gradually included in piglet feeding practices. These additives are safe, non-toxic and efficient; therefore, they have become a popular topic of discussion and study among animal nutritionists (Le et al 2016;Missotten et al 2016;) Among them, fermented lactic acid bacteria feed has been the most widely used in recent years (Missotten et al 2009;Lin et al 2010). However, researchers have found that piglets weaned using a large amount of fermented lactic acid bacteria feed were prone to diarrhoea.…”
Section: Introductionmentioning
confidence: 99%